Implementasi Konsep Tanggung Jawab Sosial sebagai Upaya Meningkatkan Efektivitas Pengelolaan BUMDes - Agustina, Iin; Pradesa, Hafid Aditya (Jurnal Manajemen dan Kewirausahaan, 2020)
This study aims to initiate a model for the social responsibility framework of BUMDes. This research has the aim of initiating a model for the social responsibility framework of BUMDes, by considering its institutional structure as a strategic business entity and becoming one of the main pillars for developingÂ the economic potentialÂ in rural areas. Considering stakeholders from BUMDes and the social responsibility domain framework based on the Triple Bottom Line concept, the potential impact of BUMDes existence is well recognized and the social responsibility domain for BUMDes is offered in this article. The practice of social responsibility for BUMDes has not become an interesting area or even has an urgency to be studied. Eventhough, BUMDes is the dominant engine of economic growth - creators of value principles and managerial resources - and that BUMDes have an obligation to contribute to the economic growth of rural communities - encourages the need to promote sustainability among stakeholders and increase the sustainability of business that managed by BUMDeshttps://doi.org/10.26905/jmdk.v8i2.4768